Graded radical W type Lie algebras I - Ki-Bong Nam (International Journal of Mathematics and Mathematical Sciences)
We get a new ℤ-graded Witt type simple Lie algebra using a generalized polynomial ring which is the radical extension of the polynomial ring F[x] with the exponential function ex.